PERAN PANTI ASUHAN TUNAS BANGSA DALAM UPAYA MENINGKATKAN KESEJAHTERAAN ANAK ASUH MELALUI PENDIDIKAN INFORMAL - Octafitri, Amelia; Punia, I Nengah; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This study focuses on the informal education of children in orphanages. This research explains the Role of the Tunas Bangsa Orphanage in an Effort to Improve Foster Child Welfare through Informal Education. The background in this research is the application of informal education which is the main thing for the children at the Tunas Bangsa Orphanage and the suitability of informal education for the welfare of the Tunas Bangsa Orphanage's children. Based on these problems This study uses descriptive and explanative types aim to describe social action from Tunas Bangsa Orphanage. The theory used is social action theory of Max Weber. The results of activity process consists of three systems The Tunas Bangsa. The results of this research suggest that the Tunas Bangsa Orphanage should present a father figure. Key words: Orphanage, Child Welfare, Informal Education, Education System